Evaluation of Immunogenicity of Nivolumab Monotherapy and Its Clinical Relevance in Patients With Metastatic Solid Tumors. (27th September 2016) - Agrawal, Shruti; Statkevich, Paul; Bajaj, Gaurav; Feng, Yan; Saeger, Sally; Desai, Dharmesh D.; Park, Jong‐Soon; Waxman, Ian M.; Roy, Amit; Gupta, Manish
Abstract: Nivolumab is a fully human IgG4 monoclonal antibody targeting the programmed death‐1 (PD‐1) receptor that blocks interactions between PD‐1 and its ligands on tumor cells to prevent T‐cell exhaustion in patients with cancer. It has demonstrated efficacy in multiple tumor types, including melanoma, non‐small‐cell lung cancer, and renal cell carcinoma. This analysis assessed the immunogenicity of nivolumab and its impact on pharmacokinetics, safety, and efficacy in patients with solid tumors enrolled in 6 clinical studies. The incidence and prevalence of antidrug antibodies (ADAs) were determined by validated electrochemiluminescence assays in samples collected during nivolumab treatment and up to 100 days after the last dose. Confirmed positive samples from the 6 studies were also tested for presence of neutralizing antibodies (NAbs). Among 1086 nivolumab‐treated patients, 138 patients (12.7%) were ADA positive (relative to baseline), only 3 (0.3%) of whom were persistently positive for ADA, and 9 (0.8%) were NAb positive at 1 time point. The presence of ADAs was not associated with hypersensitivity, infusion reactions, or loss of efficacy and had minimal impact on nivolumab clearance. Additionally, the presence of NAbs was not associated with loss of efficacy. In conclusion, immunogenicity of nivolumab is not clinically meaningful.